2002
DOI: 10.1139/s02-013
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing sediment sources and natural hydrocarbon inputs in the lower Athabasca River, Canada

Abstract: The Athabasca River drains an area of 160 000 km2 in northern Alberta, Canada, with much of the lower basin underlain by oil-sand deposits. The oil sands occur primarily in the McMurray Formation of the Cretaceous Period, with outcrops evident along the banks of the Athabasca River, as well as the lower portions of several tributaries. Since the oil sands represent a natural diffuse source of hydrocarbons to the aquatic environment, understanding the nature and extent of sediment-bound hydrocarbon contaminants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 16 publications
3
48
0
Order By: Relevance
“…1). The Athabasca River is exposed to the McMF 50 km upstream of Fort McMurray and is present within its banks to Eymundson Creek (38).…”
Section: Methodsmentioning
confidence: 99%
“…1). The Athabasca River is exposed to the McMF 50 km upstream of Fort McMurray and is present within its banks to Eymundson Creek (38).…”
Section: Methodsmentioning
confidence: 99%
“…3). Previous reports indicated that differences in water quality along tributaries of the Athabasca River were due to the influence of incisement of the rich bitumen beds in the McMurray Formation (e.g., Conly et al 2002Conly et al , 2007Headley et al 2001Headley et al , 2005Alberta Government 2010). However, prior studies were substantially shorter in duration and spatial extent than the 38 year study described here.…”
Section: Establishing Reference In the Oil Sands Regionmentioning
confidence: 99%
“…Bitumen, a form of heavy crude oil, contains particulate organic material, hydrocarbons, associated metals, and sulfur compounds (WHO 2004). Earlier assessments (2001)(2002)(2003)(2004)(2005)(2006)(2007) attributed the presence of contaminants and heavy metals in the Athabasca River and its tributaries to natural erosion of the geological strata that contain bitumen (e.g., Conly et al 2002Conly et al , 2007Hedley et al 2001Hedley et al , 2005. The Alberta Government (2010) concluded, "there has been no increase in concentrations of contaminants as oil sands development has progressed."…”
Section: Introductionmentioning
confidence: 99%
“…1), oil-sand material can be found within 75 m of the surface and portions of the oil and deposits are exposed, especially along the banks of the Athabasca River, as well as the lower portions of several tributaries, where rivers have incised into the McMurray Formation. [6] The erosion of the exposed oil sands deposits has distributed hydrocarbons throughout the region's river system and these hydrocarbons arising from natural processes may be referred to as naturally derived hydrocarbons. [7] Heavy metals and major ions co-occur with elevated levels of naturally occurring petroleum hydrocarbons and complex mixtures of naphthenic acids.…”
Section: Introductionmentioning
confidence: 99%